The Importance of Introducing Adult Adoption in the Family Law of Ethiopia: Some Points from the Experience of Other Jurisdictions - Mekonnen, Nega Ewunetie (Bahir Dar University Journal of Law, 2023)
Adult adoption had a place in ancient laws, including Roman law. It was also recognized by the French Napoleonic Law of 1804, which was used as a source for the European continental legal system and the 1960 Civil Code of Ethiopia. The concept of adult adoption in Napoleon's law was transplanted in the modern laws of France, Spain, Italy, Germany, and other European countries; it used widely used in the family laws of the United States and other Common law legal systems. Even though adult adoption in Ethiopia had a historical, cultural, traditional, and social basis, the 1960 Civil Code of Ethiopia did not only fail to recognize it but also repealed it with other existing customary laws of the country. The federal and regional state family laws, based on the 1960 Civil Code of Ethiopia, follow a similar pattern. This researcher argues that there are historical, cultural, traditional, social, and legal reasons for allowing adult adoption in Ethiopia. Based on these reasons, the researcher recommends the amendment of the existing family law and the introduction of adult adoption in the Ethiopian legal system.